Estudo do conversor cc-ca a quatro fios com capacitor dividido conectado à rede com desequilíbrio de carga - Silva, Alex Ferreira (Universidade Federal de São Carlos, 2021)
The three-phase dc-ac converters based on power electronics are the main equipment used to connect renewable sources to the electricity distribution system. The three-phase four-wire distribution system with voltage unbalance has undesired negative and zero sequence components, which can cause several negative impacts to the system. Among these impacts, it stands out as synchronism failures between the dc-ca converter and the electrical grid, which is normally done through Phase Lock Loop (PLL). The Synchronous Reference Frame-PLL (SRF-PLL) is it used. However, this method does not perform well when the electrical grid has voltage unbalance, since negative and zero sequence components are present in the unbalanced system. There are PLLs that can be used, within certain operating limits, in an electrical grid with voltage imbalance, such as Dual Second Order Generalized Integrator-PLL (DSOGI-PLL) that allows the synchronism between the converter cc-ca and the mains even in conditions of voltage imbalance. In this work, the performance of SRF-PLL and DSOGI-PLL is studied when the cc-ca converter is subjected to several imbalance factors. The simulation results are obtained, bulletin with the balanced system. In addition, the system was simulated with unbalanced loads, considering some operating situations. The main conclusion obtained is that the cc-ca converter can inject sinusoidal currents into the electrical grid up to a certain operating limit using the DSOGI-PLL
Converter study cc-ca four-wire with split capacitor connected to grid with unbalance of charge
Keywords: Eletrônica de potência; Desequilíbrios de tensão; Conversores cc-ca trifásicos; SRF-PLL; DSOGI-PLL; Power Electronics; Voltage unbalanced; Three-phase dc-ac converters; SRF-PLL; DSOGI-PLL; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS